A comparative study of optic disc detection methods on five public available database - Veras, Rodrigo; Medeiros, Fátima; Santos, Luckas dos; Sousa, Fernando (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2014: Anais do XIV Workshop de Informática Médica, 2014)
Fundus images are valuable resources in eye diagnosis. Thus, processing and analysis of these images constitute a relevant task to aid eye specialists. Particularly, finding the Optic Disk (OD) in a retinal fundus image improves significantly the chances to detect eye diseases. In fact, the OD location can be input for algorithms that detect other retinal anatomical structures such as macula, blood vessels and some anomalies, such as exudates, hemorrhages and drusen. And these anomalies indicate the presence of retinal diseases. This paper compares and evaluate the performance of seven different automatic OD detection algorithms using five public benchmark image database.